Analysis Iof Ipatient Isatisfaction Iwith Ionline Ioutpatient Iregistration Iservices Iat Iwangaya Igeneral Ihospital, IDenpasar ICity - Sang Made Baskara Dinata; Nurul Faidah; Made Wahyu Aditya (International Journal of Health Engineering and Technology, 2025)
Online ipatient iregistration isystems ihave ibeen iintroduced iin imany ihospitals ito iimprove iefficiency iand iconvenience. iAt iWangaya iRegional iGeneral iHospital i(RSUD iWangaya), ithe iOnline iRegistration iSystem i(APDOL) ihas ibeen iimplemented isince i2022, ibut ipatient isatisfaction ihas inot iyet ibeen ievaluated. iThis istudy iaimed ito ianalyze ipatient isatisfaction iwith iAPDOL iin ithe ioutpatient iregistration iunit. iA idescriptive iquantitative idesign iwith ia icross-sectional iapproach iwas iused. iThe ipopulation iconsisted iof i811 iAPDOL iusers iin iNovember i2024, iand ia isample iof i90 ipatients iwas iselected ithrough isimple irandom isampling. iData iwere icollected iusing ipatient isatisfaction iand iAPDOL iquality iquestionnaires, ithen ianalyzed iwith iunivariate istatistics. iResults ishowed ithat i80% iof irespondents irated ithe isystem iquality ias igood iand i20% ias isufficient. iRegarding isatisfaction, i70% iof ipatients iwere isatisfied, iwhile i30% ireported ilower isatisfaction. iReliability iand iaccessibility iwere ithe imost ipositively irated iaspects, iwhereas itimeliness irequired iimprovement. iIn iconclusion, iAPDOL igenerally imet ipatient iexpectations, ibut ienhancements iin iresponsiveness iand iuser-friendliness iare istill ineeded ito ifurther iimprove isatisfaction iand iservice iquality.